Emerging Issues and Potential Opportunities in the Rice–Wheat Cropping System of North-Western India - Dhanda, Sachin; Yadav, Ashok; Yadav, Dharam Bir; Chauhan, Bhagirath Singh (Frontiers in Plant Science, 2022)
The rice-wheat cropping system (RWCS) is the backbone of Indian farming, especially in the north-western region. But continuous adoption of the RWCS in northwest India has resulted in major challenges and stagnation in the productivity of this system. Additionally, the Indo-Gangetic Plains of Pakistan, Nepal, and Bangladesh are also facing similar challenges for sustainable production of the RWCS. Several emerging problems, such as the exhausting nutrient pool in soil, deteriorating soil health, groundwater depletion, escalating production cost, labor scarcity, environmental pollution due to crop residue burning and greenhouse gas emissions, climatic vulnerabilities, and herbicide resistance in weed species are a few major threats to its sustainability. To address these challenges, a wide range of sustainable intensification technologies have been developed to reduce the irrigation and labor requirements, tillage intensity, and straw burning. Awareness and capacity building of the stakeholders and policy matching/advocacy need to be prioritized to adopt time- and need-based strategies at the ground level to combat these challenges. This review summarizes the current status and challenges of the RWCS in the northwest region of the country and also focuses on the precision management options for achieving high productivity, profitability, and sustainability.